2020
DOI: 10.1108/ijm-01-2020-0038
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation in pay for performance within organizations: an occupational perspective

Abstract: PurposeThis study aims to address the question of why organizations do not uniformly apply pay for performance (PFP) throughout the organization, focusing on the wider occupational structure in which they and the jobs they create are embedded. The authors propose a model of “occupational differentiation” whereby the probability of a job within a given organization having PFP increases with the levels of monitoring difficulty and requisite human asset specificity characterizing the occupation to which a job bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Moreover, PFP can act as a way to retain valuable specific human capital as a form of ‘efficiency wage’ (Akerlof, 1982). Empirical research has generally found PFP-use is greatest where work is difficult to monitor and where human asset specificity is high (Williams et al, 2019). Indeed, PFP is often taken as an indicator of the service relationship, while overtime pay is an indicator of the labour contract characterized by discrete amounts of effort for discrete amounts of reward (Evans and Mills, 1998, 2000; Zou, 2015).…”
Section: Occupational Class and The Rise In Pay For Performancementioning
confidence: 99%
“…Moreover, PFP can act as a way to retain valuable specific human capital as a form of ‘efficiency wage’ (Akerlof, 1982). Empirical research has generally found PFP-use is greatest where work is difficult to monitor and where human asset specificity is high (Williams et al, 2019). Indeed, PFP is often taken as an indicator of the service relationship, while overtime pay is an indicator of the labour contract characterized by discrete amounts of effort for discrete amounts of reward (Evans and Mills, 1998, 2000; Zou, 2015).…”
Section: Occupational Class and The Rise In Pay For Performancementioning
confidence: 99%